El desarrollo de la motricidad fina y su influencia en la lecto escritura de los niños, niñas del primer año de la educación básica de la escuela la Providencia del cantón Machala, periodo lectivo 2011-2012. - Ordoñez Mora, Danis Alexandra (2012)
This proposal aimed at assisting in the development of the reading and writing of children in the first year of basic education, consists of an album of technical graphical techniques, called document supporting the intervention proposal, also indicates the theoretical foundations , The organization, the objectives pursued, the activities to be carried out and how the proposal will be evaluated.